2014
DOI: 10.2807/1560-7917.es2014.19.24.20832
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Health Protection Event-Based Surveillance for the London 2012 Olympic and Paralympic Games

Abstract: The Health Protection Agency (HPA) (currently Public Health England) implemented the Health Protection Event-Based Surveillance (EBS) to provide additional national epidemic intelligence for the 2012 London Olympic and Paralympic Games (the Games). We describe EBS and evaluate the system attributes. EBS aimed at identifying, assessing and reporting to the HPA Olympic Coordination Centre (OCC) possible national infectious disease threats that may significantly impact the Games. EBS reported events in England fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 14 publications
0
18
0
1
Order By: Relevance
“…16 Implementation of event-based surveillance at the global level is well-established in WHO, ECDC, and the US Centers for Disease Control and Prevention (CDC). 47 , 48 While event-based surveillance implementation during mass gatherings has been described, 35 , 49 , 50 event-based surveillance integration is not common at the national level 51 and has been recently recommended by WHO. 47 As in previous mass-gathering experiences, 49 the national Italian event-based surveillance system had a complementary role to existing indicator-based surveillance systems, acting as a safety net.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Implementation of event-based surveillance at the global level is well-established in WHO, ECDC, and the US Centers for Disease Control and Prevention (CDC). 47 , 48 While event-based surveillance implementation during mass gatherings has been described, 35 , 49 , 50 event-based surveillance integration is not common at the national level 51 and has been recently recommended by WHO. 47 As in previous mass-gathering experiences, 49 the national Italian event-based surveillance system had a complementary role to existing indicator-based surveillance systems, acting as a safety net.…”
Section: Discussionmentioning
confidence: 99%
“…47 , 48 While event-based surveillance implementation during mass gatherings has been described, 35 , 49 , 50 event-based surveillance integration is not common at the national level 51 and has been recently recommended by WHO. 47 As in previous mass-gathering experiences, 49 the national Italian event-based surveillance system had a complementary role to existing indicator-based surveillance systems, acting as a safety net. Pending a formal evaluation of the event-based surveillance system, both in relation to the EXPO 2015 mass gathering and more generally to public health in Italy, the surveillance results suggest that the system was useful in providing additional real-time evidence that no health emergencies were occurring during EXPO.…”
Section: Discussionmentioning
confidence: 99%
“…A summary of our literature review of the existing IDS systems is shown in Table 1. Through analyzing the common and central aims of selected studies, we have identified 3 fundamental requirements for infectious disease reporting systems, which is the ability to capture and report outbreak data accurately, completely, and in a timely fashion [19][20][21][22][23][24][25]. Fundamental requirements were also used as the basis for identifying subsequent specific user requirements.…”
Section: Phase 1: Literature Review Of the State Of The Artmentioning
confidence: 99%
“…Ademais, sabendo-se que a estratégia de vigilância baseada em eventos é preconizada pela OMS com a finalidade de alerta e resposta rápida às emergências em saúde pública 15 e que tal estratégia foi aplicada durante os Jogos Olímpicos de Londres 2012, sendo avaliada como útil, aceitável, estável e confiável 16 , recomenda-se que os processos de trabalho do CIEVS/MS sejam sistematizados e fortalecidos para a adequada vigilância das emergências em saúde pública no Brasil, inclusive, para o monitoramento das potenciais emergências em saúde pública durante os eventos de massa 17 , como a Copa do Mundo e os Jogos Olímpicos.…”
Section: Conclusãounclassified